Lärarnas åsikter och förberedelser inför Move! -mätningarna - Wilén, Linus (2018)
The purpose with this thesis was to find out what teachers think of the Move!-measurements. The study also brings up how teachers prepare themselves and the students before the measurements, the teacher’s opinions about the measurements’ content as well as how will the students perform in the measurements according to the teachers. The aim was also to get out of this information, new ideas and suggestions how to improve the Move!-measurements. This research used a qualitative method. The interviews was based on different themes and had both structured and unstructured features. Six teachers participated in the interviews. They all teach physical education for 7th to 9th grade. I chose to focus on teachers who only teach for these grades because the Move!-measurements weren’t obligatory when the research was done. The interviews took place in autumn 2017 and the Move!-measurements will not be mandatory for 8th graders until autumn 2018. The teachers came from three different schools from two different municipalities. Because of this I got a wider view on what the teachers think about the measurements and at the same time answers for the question, are there any disparities in the preparations towards the measurements due to in which municipality you work for. The interviews was made in Swedish as well as the thesis which focused on teachers who teach in Swedish speaking schools. This was also a reason to interview teachers from other municipalities to get teachers who fulfilled the criteria. I put the research’s different purposes as themes for the interviews. I categorized the data in different themes, did a material – content analysis and classified the answers. The research showed that the interviewed teachers prepare themselves well before the measurements, they are giving information about the measurements to the students on 7th grade and also practice the moves that Move! contains. According to this research there are differences in the preparations towards the measurements between schools. In some schools they have been doing the Move!-measurements for some years and in other schools they hadn’t done anything specific as of autumn 2017. The majority of the teachers who I interviewed felt there should be changes made in the content of Move! The pushups got a lot of criticism. The teachers felt that the content should contain moves that are hard to cheat. They thought that the results are going to be misleading because of cheating, having a classmate doing the judgement, the teachers aren’t following the same line, different surroundings and that all students results aren’t send forward to national analysis. This means that there are going to be differences in the measurements because of the reasons mentioned above. The research also showed that the cooperation between the teachers and the school nurse is not working. According to this research, the teachers will get more experience due time and therefor will the measurements proceed better. And if the students get to practice on the moves, they will perform them more correctly. The principle should give strict instructions to everybody who is involved in Move!, so that the cooperation runs better. Key words: Move!, physical activity, physical tests, curriculum 2014